Consumer Protection Efforts and Innovation for Sustainable Income in Halal MSMEs from the Perspective of Sharia Economic Law: A Case Study of Teh Bunga Sedap Malam - Firza Agung Prakoso; Tristan Rokhmawan; Reviandy Azhar Ramdhani; Dadang Husen Sobana (Journal of Islamic Economics and Business, 2025)
This research examines halal product consumer protection within the framework of Sharia Economic Law while empirically analyzing the role of creativity and innovation in supporting sustainable income among halal-based micro, small, and medium enterprises (MSMEs), with a specific focus on Teh Bunga Sedap Malam at Pasar Rembang, Pasuruan. This study adopts a quantitative explanatory research design to identify the causal relationship between creativity, innovation, and income generation. A total of 55 respondents were selected using purposive sampling based on eligibility criteria, and structured questionnaires using a Likert scale were distributed to obtain primary data. The collected data were processed through validity and reliability testing, classical assumption testing, and multiple linear regression analysis to determine the partial and simultaneous influence of creativity and innovation on MSME income. The findings reveal that both creativity and innovation have a positive and significant effect on income, indicating that the ability of MSME actors to develop ideas and transform them into innovative business practices plays a crucial role in enhancing business performance and ensuring financial sustainability. From a Sharia economic perspective, strengthening creativity and innovation must also be aligned with halal assurance, fairness, transparency, and ethical business practices to ensure consumer protection and compliance with Islamic economic values. The study contributes theoretically by integrating empirical income-based analysis with normative Sharia consumer protection principles and practically by providing strategic recommendations for strengthening MSME capacity, regulatory support, and halal awareness. Future research is recommended to expand the sample scope and explore additional determinants influencing MSME sustainability in the halal economic ecosystem.